Zigbee Based Universal Motor Speed Control and Monitoring System - M.Divya; Dr. V. S. Srinivasan (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The ZigBee-Based Universal Motor Speed Control and Monitoring System presents an innovative approach to managing and regulating motor speeds across various applications. Leveraging the ZigBee wireless communication protocol, this system enables remote control and real-time monitoring of motor performance, enhancing operational efficiency and flexibility. The system consists of a ZigBee module for wireless communication, a microcontroller for processing and control, and an interface for adjusting motor speed settings. It integrates sensors to monitor motor parameters such as speed, temperature, and load, which are transmitted wirelessly to a central control unit or mobile device for analysis and visualization. The primary objectives of this system are to provide precise speed control, improve monitoring accuracy, and offer remote access to motor status. By utilizing ZigBee’s low-power, reliable communication capabilities, the system ensures efficient and uninterrupted performance across diverse industrial and domestic environments. The implementation of this technology not only simplifies motor control processes but also facilitates proactive maintenance and performance optimization, making it a valuable solution for modern automation and control systems.